A full medical service for all : BMA's national plan
1938-04 1938 1930s 3 pages - 2 - economically filled; and important changes in local government administration to assist the smooth working of the scheme. ROLE OF THE FAMILY DOCTOR Paras. 29-34 The basis of the whole scheme is that there should be available for every individual a family doctor of his own choice. The necessity for "free choice" is emphasized on the score of confidence as between doctor and patient. The special importance of the family doctor may be summed up in the four words "entry to the home". Because of his intimate knowledge of the homes and lives of his patients, it is stated, "he has unrivalled opportunities to advise on healthy living, to take into account domestic circumstances and environment, and to discover as early as possible when departures from the normal have occurred." The doctor is his patient's guide to all other forms of medical service, and liaison officer between them and him. FOUR GUIDING PRINCIPLES Para. 24 The basic principles of the B.M.A. scheme are listed as follows:- (1) "That the system of medical service should be directed to the achievement of positive health and the prevention of disease no less than to the relief of sickness. (2) "That there should be provided for every individual the services of a general practitioner or a family doctor of his own choice (as above). (3) "That consultants and specialists, laboratory services, and all necessary auxiliary services, together with institutional provision when required, should be available for the individual patient, normally through the agency of the family doctor. (4) "That the several parts of the complete medical service should be closely co-ordinated and developed by the application of a planned national health policy." 292/847/1/59